Low pass-through from inflation expectations to income growth expectations: Why people dislike inflation - Ina Hajdini; Edward S. Knotek; John Leer; Mathieu Pedemonte; Robert W. Rich; Raphael Schoenle (Inter-American Development Bank (IDB), 2025)
Using a large, nationally representative survey of US consumers, we estimate a causal 20 percent pass-through from inflation expectations to income growth expectations for the average consumer, with considerable heterogeneity in pass-through associated with sociodemographic factors. The results also indicate that higher inflation expectations cause an increase in consumers' likelihood to search for higher-paying jobs but do not change the likelihood of asking for a raise, suggesting that consumers recognize significant wage rigidity with their current employer. In a calibrated search-and-matching model, we find that demand and supply shocks combined with incomplete pass-through produce a strong negative relationship between expected inflation and expected utility. Taken together, the survey results and model analysis provide a labor market account of why people dislike inflation.
Keywords: E31; E24; E71; C83; 330; Inflation; Wage-price spiral; Expectations; Randomized controlled trial